Trio Album for violin, violoncello & piano - ALBENIZ, I [et.al.] (The Boston Music Co.)
Tango in DnMinuetnBy the BrooknPrelude in AbnPassepiednSerenadenTold at TwilightnValser gentilenInterlude orientalnElegy